Efektivitas Metode Simulasi Total Physical Response pada Praktik Terbang Pre Solo - Agung Wahyu Wicaksono; Stephen Huibert Daniel Agu; Arya Yuda Prawira (SKY EAST: Education of Aviation Science and Technology, 2025)
Pilot training is a complex and demanding process, especially in the pre-solo phase where student pilots must master various technical and non-technical skills before being allowed to fly solo. One potential method to use is the Total Physical Response (TPR) method, which at the Indonesian Civil Pilot Academy of Banyuwangi is often referred to as "dryswim". This study uses a qualitative research method with a phenomenological analysis approach to explore how student pilots experience and perceive the use of the Total Physical Response (TPR) method during the pre-solo phase. The total population is 71 student pilots who have passed the pre-solo phase. The sample / informants in this study will be selected purposively with the main criteria being student pilots who most often use the Total Physical Response (TPR) or dryswim method during their training. The respondents / informants selected were 8 people from each class. The results of the study stated that many student pilots felt that Total Physical Response was effective and practical, especially if done consistently, and this was very helpful for those who still had difficulty in various aspects of flight such as landing and memorizing circuit procedures. In addition, Total Physical Response helps the body get used to the movements that are in accordance with the procedure, so that the brain can focus more on other aspects, increase self-confidence, and make flying smoother and more efficient.